Constructing Based Mathematics Learning Bruner's Theory to Improve Learning Outcomes Grade IV students at SD Negeri 15 Ternate City - Malinda Fatah (Scientechno: Journal of Science and Technology, 2024)
This study aims to construct learning mathematics based on Bruner's theory to improve the learning outcomes of fourth grade elementary school students in studying the material for adding fractions with different denominators. The research approach used is a qualitative approach with a class action research design (CAR). Place of research, in SD Negeri 15 Kota Ternate. The subjects in this study were 4 students, taken one high ranking student, two medium ranking students, and one low ranking student. Data collection techniques in this study were student ability tests, observations, and interviews. The collected data were analyzed qualitatively and quantitatively. This research was conducted in 3 learning actions. Based on the results of this study it is suggested (1) in teaching fraction addition operations material, the teacher needs to relate the knowledge that students already have, namely the concept of fractions and the concept of equivalent fractions, (2) to teach the concept of arithmetic operations for adding fractions with different denominators, the teacher should make a learning plan through three stages of presentation namely the enactive stage, the iconic stage, and the symbolic stage by using a variety of teaching methods so that it is fun for students, (3) the teacher needs to know the difficulties and causes in learning the arithmetic operations of adding fractions with different denominators, and(4) the results of this study can be used as reference material for researchers, teachers who teach mathematics in elementary schools.